Negosiasi Ruang Sakral: Analisis Fatwa MUI No. 34 Tahun 2013 di Kota Medan dalam Perspektif Mashlahah Mursalah - Lauhin Mahfudz; Tanjung, Dhiauddin; Siregar, Ramadhan Syahmedi (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2025)
This article analyzes the implementation of the Indonesian Council of Ulama (MUI) Fatwa No. 34 of 2013 concerning the conduct of marriage contracts (akad nikah) in mosques in the city of Medan, examining the socio-religious dynamics through the lens of maslahah mursalah (consideration of public benefit). The fatwa emphasizes the importance of preserving the sanctity of the mosque as a place of worship by upholding proper Islamic etiquette, such as dressing modestly, avoiding overpowering fragrances, and maintaining order and reverence. However, in practice, numerous violations of these norms occur, revealing ongoing negotiations between the demands of Islamic law and the social customs of urban communities, particularly concerning appearance and clothing styles during marriage ceremonies. These violations not only blur the sacred value of marriage as an act of worship but also risk desecrating the honor of the mosque as a sacred space. This research adopts a qualitative approach using field research methods, which include direct observation of marriage ceremonies in several mosques in Medan, in-depth interviews with religious leaders, mosque administrators, marriage officiants (penghulu), and members of the general public, as well as an examination of documents related to the MUI fatwa. The data are analyzed descriptively and critically within the framework of maslahah mursalah theory to identify patterns of violation, institutional responses, and potential solutions. From the maslahah mursalah perspective, preserving the sanctity of the mosque constitutes a primary necessity (daruriyah), as it is closely linked to the protection of religion (hifzh al-din). The study recommends public education initiatives led by religious figures, the development of etiquette guidelines for mosque-based marriage ceremonies, and administrative oversight by marriage registrars and the Office of Religious Affairs (KUA) to ensure that marriage contracts conducted in mosques are not merely ceremonial but also reflect a deep respect for Islamic sacred values. Thus, the implementation of this fatwa becomes a site of negotiation between religious authority, social norms, and the community’s religious consciousness.